About the Pros and Cons of Democratic State – Legal Regimes - Vladimir Valentinovich Kozhevnikov (Polit Journal Scientific Journal of Politics, 2021)
This scientific article is devoted to the characteristics of the liberal-democratic and proper democratic state-legal regimes, which have both positive and negative properties. Speaking about a proper democratic state-legal regime, it is argued that this is an ideal that any society and state strives to achieve.